Uncovering and Redesigning a Key Amino Acid of Glucose Oxidase for Improved Biotechnological Applications. Issue 3 (24th January 2013) - Suraniti, Emmanuel; Courjean, Olivier; Gounel, Sébastien; Tremey, Emilie; Mano, Nicolas
Abstract Here we uncover a key amino acid at the entrance of the active site of glucose oxidase from Penicilium amagasakiense and we successfully redesign it by nonactive site mutations, leading to enzymatic anodes with 2.4 fold higher current densities. The increase in current density could be correlated with a better interaction between the negatively charged amino acid located in position 424 and the positively charged redox mediator. We also demonstrate that this increase in current was not specific to Osmium and that further introduction of negative charges around the active site of glucose oxidase lead to a decrease in current density, illustrating the uniqueness of this amino acid in position 424.